Biocontrol: Endophytic bacteria could be crucial to fight soft rot disease in the rare medicinal herb, Anoectochilus roxburghii. Issue 12 (13th September 2022) - Xing, Bingcong; Zheng, Ying; Zhang, Man; Liu, Xinting; Li, Lihong; Mou, Chenhao; Wu, Qichao; Guo, Haipeng; Shao, Qingsong
Abstract: Microbial destabilization induced by pathogen infection has severely affected plant quality and output, such as Anoectochilus roxburghii, an economically important herb. Soft rot is the main disease that occurs during A. roxburghii culturing. However, the key members of pathogens and their interplay with non‐detrimental microorganisms in diseased plants remain largely unsolved. Here, by utilizing a molecular ecological network approach, the interactions within bacterial communities in endophytic compartments and the surrounding soils during soft rot infection were investigated. Significant differences in bacterial diversity and community composition between healthy and diseased plants were observed, indicating that the endophytic communities were strongly influenced by pathogen invasion. Endophytic stem communities of the diseased plants were primarily derived from roots and the root endophytes were largely derived from rhizosphere soils, which depicts a possible pathogen migration image from soils to roots and finally the stems. Furthermore, interactions among microbial members indicated that pathogen invasion might be aided by positively correlated native microbial members, such as Enterobacter and Microbacterium, who may assist in colonization and multiplication through a mutualistic relationship in roots during the pathogen infection process. Our findings will help open new avenues for developing more accurate strategies for biological control of A. roxburghii bacterial soft rot disease. Abstract : The onset of Anoectochilus roxburghii soft rot began in bulk soils, migrated into the roots. The endophytic communities were strongly influenced by pathogen invasion. Pathogen invasion may be aided by positively correlated native microbial members.